Soil and rock strength parameters of the Shiraidake Landslide, Japan - Jelinek, Robert; Paudel, Prem Prasad; Omura, Hiroshi (Journal of Nepal Geological Society, 2001)
The Shiraidake area of northwest Kyushu has an extensive distribution of landslides. A series of undrained triaxial tests and unconfined compression tests were carried out to investigate the variation of strength properties in a selected borehole from the Shiraidake Landslide. It is a translational landslide (called the Hokusho-type in Japan) and is composed of the Early Tertiary and Quaternary sedimentary rocks that are prone to rapid weathering. Core rock samples and recompacted soil samples were used for the study. The results provided the fundamental characteristics of soil and rock under the triaxial and uniaxial tests, and indicated that the undrained behaviour of tested soils generally depends on the pre-shear consolidation pressure and dry density. In addition, the type of material used and the tests performed are important factors that influence the soil and rock strength.